Administering welfare reform : International transformations in welfare governance - Fenger, Menno; Henman, Paul (Book collections on Project MUSE., 2006)
While reforms of welfare policies have been widely analysed, the reform of welfare administration has received far less attention. Using empirical case studies, this book provides significant new insights into the way welfare administration is being internationally transformed. Particular attention is given to the effect on welfare clients, staff and agencies.